2015
DOI: 10.1016/j.appet.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Response of appetite and potential appetite regulators following intake of high energy nutritional supplements

Abstract: Keywords:High energy supplements Appetite Appetite hormones Gastric emptying Thermogenesis Control of food intake a b s t r a c t Background:The net clinical benefit of high-energy nutritional supplements (HENSDs) consumption is lower than expected. Objectives: To investigate the extent to which consumption of oral HENSD in the fasted state reduces energy intake in slim females during consecutive breakfast and lunch, and whether this relates to changes in appetite and metabolic appetite regulators. Design: Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 30 publications
16
34
1
Order By: Relevance
“…This suggests that at least 2/3 of the energy ingested may have been compensated, by eating less at other times. We have previously shown in a well-controlled, mechanistic, energy balance study that almost half of the energy provided by ONS was compensated for by eating less during a consecutive meal [19]. Energy compensation may explain to some extent, why supplementation trials in under-or malnourished children have found that observed weight gain rate was substantially less than predicted [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that at least 2/3 of the energy ingested may have been compensated, by eating less at other times. We have previously shown in a well-controlled, mechanistic, energy balance study that almost half of the energy provided by ONS was compensated for by eating less during a consecutive meal [19]. Energy compensation may explain to some extent, why supplementation trials in under-or malnourished children have found that observed weight gain rate was substantially less than predicted [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate combined effect of both PKU protein substitute and meals based on special low protein foods on research outcomes of this study. The responses of gut hormones were measured in a subset of the volunteers since research previously conducted by us [29] and others [15,18] has shown that using this number allowed identification of meaningful and statistically significant differences in plasma concentrations of PYY and GLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] Moreover, consumption of dietary supplements containing multivitamins and minerals can improve the appetite. [ 12 ] Thus, anorexia as a prevalent outcome of hospitalization can be prevented to some extent and patients would receive more energy and macronutrients, subsequently. [ 12 ] Finally, it may reduce the malnutrition and death rate in the hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Thus, anorexia as a prevalent outcome of hospitalization can be prevented to some extent and patients would receive more energy and macronutrients, subsequently. [ 12 ] Finally, it may reduce the malnutrition and death rate in the hospitals. [ 12 ] Besides the treatment of primary disease, providing the energy requirement of the tissues and organs is the most significant action to rehabilitate the malnourished patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation